Pawns in Their Game: Bob Dylan’s Celebrity Persona in Dont Look Back - Viser, Victor (Cinémas, 2016)
Documentary film craft in the mid-twentieth century, like many other arts at the time, evolved aesthetically around the notions of “truthfulness” and “honesty” in the depiction of their subjects. Simultaneous with these artistic innovations was the ascendency of a commercial popular culture industry that often appropriated aesthetic ideals of authenticity to construct celebrity narratives. This article examines the constructed celebrity persona of Bob Dylan in D.A. Pennebaker’s American cinéma vérité production Dont Look Back. Utilizing a critical theory approach based on the philosophy and political economy of celebrity aura, it addresses questions of directorial subjectivity, celebrity self-consciousness and the contemporaneous subject/audience interface within a larger discussion of the intentionality of celebrity construction as part and parcel of films and other media dedicated to documenting the rise of pop superstars. While Dont Look Back attempts to reify Dylan as a rebellious voice speaking the social concerns of his audience, the film also testifies to the commodification of such stars by a 1960s corporate media machinery whose ultimate intentions were not necessarily so public-spirited.